The Top-Cited Articles With a Focus on Barrett's Esophagus: A Bibliometric Analysis - Gan, Peiling; Fan, Wentao; Zhang, Hailong; Zhong, Chunyu; Xia, Huifang; Lü, Muhan; Zhou, Xian; Tang, Xiaowei (Frontiers in Surgery, 2022)
Background: Because the number of published literatures with a focus on Barrett's esophagus (BE) that researchers must be familiar with has quickly increased in recent years, the significance of selective searching and summarization of bibliometrics is also increasing. It is, thus, very important to find a method that can quickly and effectively search the most influential medical science articles. Therefore, the objective of this study was to use bibliometric analysis to assess and characterize the most influential articles involving BE research. Methods: Publications on BE research were retrieved from the Web of Science Core Collection using the term “Barrett's esophagus.” Microsoft Excel 2016 and VOSviewer were used to further analyzed each article's citation number, title, journal, country, organization, category, and authorship. Results: On 14 June 2020, 5389 records of BE research published until 2020 were retrieved. The citation number of the top 100 most-cited articles ranged from 208-824. Gastroenterology published 29 articles, which accounted for the largest number of top 100 articles (29%); however, among the top 500 most-cited articles, the American Journal of Gastroenterology published the largest number. Of the top-cited articles, the USA was by far the leading country in BE research and contributed most of the articles (n=72). Among the academic institutions that produced the top 100 most-cited articles, the University of Washington (n=12) was dominant. Sharma Prateek (n=6) authored the largest number of most-cited articles. The USA contributed the most articles per year, and the time trend of the number of top 500 articles increased by 38-fold between 1987 and 2000. “Adenocarcinoma,” “high-grade dysplasia,” “cancer,” “diagnosis,” and “dysplasia” were the most influential keywords. Conclusions: This study not only presents a historical perspective but also facilitated the recognition of the significant advances in this area by researchers. Furthermore, the current study serves as a guide in decision clinical practice decision-making and provides a valuable reference for further research.